Conhecei o Brasil, crianças: representações do território brasileiro na Primeira República - Tenório, Guilherme Mendes (2014)
This research is come back toward the representations of the Brazilian territory that had circulated in some supports during the Brazil’s First Republic. Analyzing three compendiums of Geography, the programs of discipline located in Colégio Pedro II and the child seminary called O Tico - Tico, the text in such a way questions the joint between the social thought and the imaginary one come back toward the man of the interior of the country how much it evidences the signals of a valuation of the nature sidewalk in the thought, which functioned as weapon of combat to the theories that prejudice Brazil due to its natural and racial characters.